Wear-resistant Ti/TiCp composite coatings via synchronous powder supplied wire arc additive manufacturing - Xinxin Guo; Ming Ma; Shuaifeng Zhang; Zhengying Wei (Journal of Materials Research and Technology)
This study employed wire arc additive manufacturing (WAAM) with synchronous powder supplied to obtain titanium carbide (TiC) particle-reinforced titanium matrix composite coatings. The effects of welding current on the composites' microstructure evolution and wear resistance were systematically investigated. The heat erosion caused by the titanium alloy melt did not lead to the complete dissolution of the TiC particles; however, the carbon atoms at the edges of these particles diffuse into the molten pool. The resulting titanium matrix composite coatings contain residual unmelted TiC as well as in-situ precipitated TiC phases. As the current increases, the number of in-situ primary TiC grains in the matrix increases, and many coarse dendritic structures can be observed. The dry sliding friction tests revealed that the larger unmelted TiC particles help support the load and resist shear forces. Smaller primary TiC particles fill the matrix around the larger particles, further refining the microstructure and enhancing the matrix's hardness. The synergistic effect of the dual-scale reinforcement particles significantly improves wear resistance.